Studying effect of Magnesium and Aluminum ions on structural properties of M- type Barium Hexaferrite - جامع زينة; بدر الأعرج; سلامة أبو الشملات (Latakia University Journal -Basic Sciences Series, 2024)
It was prepared ferrite hexagonal BaFe12O19 pure and ferrite substitutes BaFe12-2xMgxAlxO19 with (x=0,0.5,1,2) using ceramic method .It was sintered BaFe12O19 at 1150°c for two hours .The structural characterization of the composites are investigated by x_ray diffraction device.The results obtained using XRD technology revealed the formation of the hexa-ferrite M-type hexagon with average crystal lattice constants (a=5.871,c=23,119)A°,it was found the replacement rate increased ,peak shift occurs at (114) plane to the large 2θ angle.The distance between the crystal planes d for undoped samples (2.620_2.621)A°,after it doped with aluminium and magnesium oxides decreased (2.615_2.611)A°.After sample was sintered and the sintering process causes the increasing of intensity,but decreases the FWHM value,it shows that sintering process influences the grain growth of barium hexaferrite crystals from 34.291nm to 39.902nm and it was noticed when ferrite substitutes increase the values of the crystal lattice constants decrease.